Conserving (not preserving) culture: Avoiding the damage to culture of veiled moralism in HIV education - Leigh Price (AOSIS, 2009)
Language mechanisms in much HIV discourse insist that a Western-based moralism dominates. These mechanisms include: the use of strategic absences of information about the moral grounding of texts; and slippages of meaning, where one word is used to refer to many meanings. A common slippage of meaning is the use of the word 'polygamy' to refer to a range of behaviours, thus hiding low HIV risk sexual practices (polyfidelity) under the same umbrella as high risk practices (promiscuity) and advocating their general removal. Another dubious method of achieving a moral position is to take a true premise and use it to advance a false conclusion. For example, the true premise that wife inheritance in its historical form is an HIV risk does not automatically lead to the conclusion that wife inheritance 'must' be eradicated. This is only one possible conclusion. Another, more culturally sensitive, conclusion could be that wife inheritance should be embarked upon, as should all sexual relationships, in a context of HIV tests, and safer sexual practice. I argue that moralism (such as 'wife inheritance is morally wrong') cloaked as science (the claim that science 'proves' the moral position that wife inheritance is wrong) is a threat to traditional culture and discriminates against up-holders of traditional lifestyles. Drawing primarily from my experience of HIV education in a development setting in Southern Africa, I offer a weak (realist) moral relativism as an alternative to, on the one hand, the positivist-based, absolutist morality which threatens to destroy traditional cultures in the name of HIV education and, on the other hand, extreme cultural relativism in which 'anything goes'. Possibly, HIV educators have not done enough to include some traditional safer sex practices in their professional inventory of acceptable behaviours, such as hlobonga (thigh sex) and polygamy interpreted as polyfidelity. My hope is that by being more respectful of traditional culture, whilst encouraging cultural change where necessary, HIV education will register greater success in achieving safer sexual practice. This article will be particularly useful for writers and researchers tasked with achieving behavioural change and/or tasked with writing educational materials on HIV in the Southern African context.